PERAN BIMBINGAN DAN KONSELING DALAM MENGATASI TANTANGAN ANAK DIDIKAN SUBUH DI NAGARI SUNGAI TARAB - Puspa Indah Sundari; Khotifa Khairunnisa (Counseling For All : Jurnal Bimbingan dan Konseling, 2025)
The aim of this study is to explore the role of guidance and counseling in addressing the issues faced by children participating in the Subuh education program in Nagari Sungai Tarab. The method used in this study is qualitative with a case study approach, which allows the researcher to deeply examine the dynamics occurring in this context. The research sample consists of 10 children from the Subuh education program and 2 counselors directly involved in the counseling process. The research instruments include in-depth interviews and direct observation of the counseling activities conducted. Data collection was carried out through in-depth interviews with children and counselors, as well as direct observation of the interactions and ongoing counseling activities. The collected data were analyzed using thematic analysis techniques to identify relevant patterns and themes in the guidance and counseling of the children in the Subuh education program. To ensure data validity, this study applied source triangulation, which involved comparing data obtained from different sources, as well as technique triangulation, which combined interviews and observations. The results indicate that guidance and counseling play a significant role in improving children's motivation, discipline, and religious understanding. Based on these findings, the study recommends enhancing collaboration between counselors, parents, and the community to create a more supportive environment for the Subuh education children.